Baznas Zakat Literacy in Medan Communities through Digital Communication - Nasution, Bahtiar Rivai; Syukur, Kholil; Rubino, Rubino (IAIN Ponorogo, 2024)
In the digital era 4.0, information communication and education must develop according to changing times. This research aims to analyze the digital media used by Medan’s Baznas to increase zakat literacy and explore the relationship between the level of zakat literacy and awareness in making zakat payments. This research used a descriptive method with a qualitative approach. The data were collected through interview techniques and documentation studies. Then, they were analyzed by organizing and preparing data for analysis, reading or looking at all the data, starting coding all of the data, using the coding process to generate a description, interrelating themes, and interpreting the meaning of themes. The technique for checking the validity of the data used in this research was triangulation. This research used internet culture theory and behavioristic learning theory. The research results show that the Baznas of Medan uses digital communication to increase community zakat literacy, and the corporate digital media used is Instagram. The conclusion of this research is that to get an effect/level of knowledge that can produce feedback with open behavior, people should use mainstream digital media and combine it with content with high creativity that can be adapted to the characteristics of the millennial generation.